Review of the Relationship between Anti-Hypertensive and Anti-Diabetes Drugs with Psychiatric Disorders - Hasani Sadi, Farzaneh; Saberian, Farnaz; Tajik, Mahdieh; Fallahpour, Bita (Novelty in Biomedicine, 2025)
Background: Diabetes and hypertension are two common diseases all over the world. There are several treatment options for the management of these diseases. Some studies have reported that drugs used to manage diabetes and hypertension may have an impact on psychiatric disorders such as depression and dementia. In this article, we aimed to review the results of recent studies about the impact of anti-hypertensive and antidiabetic drugs on psychiatric disorders. Materials and Methods: We reviewed studies with keywords of “diabetes”, OR “diabetic”, OR “anti-diabetes”, OR “anti-diabetes”, OR “antidiabetic”, AND “drug”, OR “hypertension”, OR “hypertensive”, OR “anti-hypertension”, OR “anti-hypertensive”, OR “anti-hypertensive”, AND “psychology”, OR “psychological” in PUBMED, ELSEVIER, and CENTRAL databases from 2015 to 2025. Results: The results of the studies were contradictory. There was no consensus idea about antidiabetic drugs, but it seems that sodium-glucose cotransporter two inhibitors can reduce the risk of depression and dementia. The results of studies about anti-hypertensive drugs had more similarities, and some anti-hypertensive drugs, like angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers, may reduce the risk of psychiatric disorders. Conclusion: There is a strong need for evaluation of the effects of anti-hypertensive and antidiabetic drugs on psychiatric disorders because the results of current studies are discrepant.